Nanofabrication of a Solid‐State, Mesoporous Nanoparticle Composite for Efficient Photocatalytic Hydrogen Generation. Issue 6 (20th May 2016) - Yamada, Yusuke; Tadokoro, Hideyuki; Naqshbandi, Masood; Canning, John; Crossley, Maxwell J.; Suenobu, Tomoyoshi; Fukuzumi, Shunichi
Abstract: Room‐temperature self‐assembly was used to fabricate a periodic array of uniformly sized Al 3+ ‐doped SiO2 nanoparticles (Al−SiO2 NPs, 20–30 nm). The uniform mesoporous structure was suitable for uniformly incorporating and distributing Pt nanoparticles (PtNPs), which were used as hydrogen‐evolution catalysts in artificial photosynthetic systems, without agglomeration during the catalytic reaction. When the surfaces of the Al−SiO2 NPs were covered with an organic photocatalyst (2‐phenyl‐4‐(1‐naphthyl)quinolinium ion, QuPh + ‐NA), each PtNP was surrounded by multiple QuPh + ‐NA ions. The structure allowed the PtNP to receive multiple electrons from QuPh . ‐NA molecules, which were generated by reduction of the photoexcited state of QuPh + ‐NA ions (QuPh . ‐NA . + ) with β‐dihydronicotinamide adenine dinucleotide (NADH), thereby resulting in efficient photocatalytic H2 evolution. Abstract : Making room : An assembly of nearly monodispersed Al 3+ ‐doped SiO2 nanoparticles (20–30 nm) that display interparticle mesospaces has been found to be suitable for incorporating Pt nanoparticles and an organic photocatalyst (2‐phenyl‐4‐(1‐naphthyl)quinolinium ion), which act as an efficient composite catalyst for photocatalytic H2 evolution (see figure).